1974
DOI: 10.1021/ac60345a003
|View full text |Cite
|
Sign up to set email alerts
|

Radioelectrochemistry. Review

Abstract: In part I of this report, we described chronocoulometric measurements of lead iodide and bromide adsorptions in which discontinuities in adsorption isotherms were related to surface solubility properties of the lead halide salts. While it is tempting to try to relate those abrupt changes in Fpb to the abrupt occurrences of inhibition observed in Part II, we believe this would be an error. We regard the two sets of observations as representing two different transitions for the adsorbed lead species. It is unfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…In several studies, influence of the radiation of tracers on electrode processes has been reported. 7 As an example, the observation of a change in the mechanism of the oxygen reduction on platinum electrodes in alkaline solutions resulting from 60Co 7 radiation should be mentioned.37 Moreover, by the incorporation of radionuclides, such as 14C, 63Ni, or 60Co, in porous carbon electrodes, an improvement of current-voltage curves has been described. 38"40 Therefore, in order to be sure that any influence from the radiation of the 59Fe marker can be excluded, the electrochemical behavior of carbon-teflon electrodes with and without iron-59-containing polyphthalocyanines have been tested.…”
Section: Resultsmentioning
confidence: 99%
“…In several studies, influence of the radiation of tracers on electrode processes has been reported. 7 As an example, the observation of a change in the mechanism of the oxygen reduction on platinum electrodes in alkaline solutions resulting from 60Co 7 radiation should be mentioned.37 Moreover, by the incorporation of radionuclides, such as 14C, 63Ni, or 60Co, in porous carbon electrodes, an improvement of current-voltage curves has been described. 38"40 Therefore, in order to be sure that any influence from the radiation of the 59Fe marker can be excluded, the electrochemical behavior of carbon-teflon electrodes with and without iron-59-containing polyphthalocyanines have been tested.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of all lead isotopes (total lead concentrations) in soil was realized by anodic stripping voltammetry (Model 797 VA, Metrohm). This method is a good method of analysis for a mixture of radioactive isotopes because it does not require the forehand knowledge to add an inactive carrier to the unknown solution as it does in most other radiochemical procedures (Katsanos et al 1966;Raaen 1974).…”
Section: Analysis Of Total Lead By Voltammetrymentioning
confidence: 99%